Allopolyploidy: An Underestimated Driver in Juniperus Evolution - Farhat, Perla; Siljak-Yakovlev, Sonja; Takvorian, Najat; Bou Dagher Kharrat, Magda; Robert, Thierry (Life (Basel, Switzerland), 2023)
Allopolyploidy is considered as a principal driver that shaped angiosperms' evolution in terms of diversification and speciation. Despite the unexpected high frequency of polyploidy that was recently discovered in the coniferous genus Juniperus, little is known about the origin of these polyploid taxa. Here, we conducted the first study devoted to deciphering the origin of the only hexaploid taxon in Juniperus along with four of its closely related tetraploid taxa using AFLP markers with four primers combinations. Phylogenetic analysis revealed that the 10 studied species belong to 2 major clusters. J. foetidissima appeared to be more related to J. thurifera, J. sabina, and J. chinensis. The Bayesian clustering analysis showing a slight variation in genetic admixture between the studied populations of J. foetidissima, suggesting an allopolyploid origin of this species involving J. thurifera and J. sabina lineages, although a purely autopolyploidy origin of both J. thurifera and J. foetidissima cannot be ruled out. The admixed genetic pattern revealed for J. seravschanica showed that the tetraploid cytotypes of this species originated from allopolyploidy, whereas no clear evidence of hybridization in the origin of the tetraploid J. thurifera and J. chinensis was detected. This study provides first insights into the polyploidy origin of the Sabina section and highlights the potential implication of allopolyploidy in the evolution of the genus Juniperus. Further analyses are needed for a more in-depth understanding of the evolutionary scenarios that produced the observed genetic patterns.
Keywords: polyploidy; hybridization; conifers; AFLP; Juniperus; genetic admixture